Formulasi dan Evaluasi Fisik Ekstrak Etanol Gel Ikan Lele (Clarias sp.) Desa Pinanong - Bunyanis, Fitriana; Yulianti, Citra; Wulandari, Nur Astuti; Jannah N, Raudhatul (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2026)
The skin is the largest organ of the human body and is prone to damage caused by external factors such as burns. One commonly used treatment is a topical gel preparation due to its ease of application and cooling sensation. This study aimed to formulate and evaluate a gel preparation containing ethanol extract of catfish (Clarias sp.) from Pinanong Village, Sidenreng Rappang Regency. The study used an experimental method with three extract concentrations: 5%, 10%, and 15%. The gels were formulated using Carbopol 940 as the base and were evaluated physically through organoleptic tests, pH, homogeneity, and spreadability tests. Stability testing was conducted by storing the gel at 4°C and 40°C for 48 hours. The organoleptic test results showed that all formulations had a semi-solid consistency with stable color and aroma throughout the storage period. The pH test indicated that Formulation 1 (5%) had the most stable pH and remained within the physiological skin pH range (4.6). The homogeneity test showed that all formulations were homogeneous, with Formulation 3 showing improved homogeneity after storage. Spreadability tests revealed that all formulations fell within the ideal range (5–7 cm), although a slight decrease was observed after storage. Based on these evaluations, Formulation 1 with a 5% extract concentration was considered the most optimal for further development as a topical gel for wound healing.